Imaging for assessment of cancer treatment response to immune checkpoint inhibitors can be complementary in identifying hypophysitis - Galligan, Anna; Iravani, Amir; Lasocki, Arian; Wallace, Roslyn; Weppler, Alison M.; Sachithanandan, Nirupa; Chiang, Cherie; Colman, Peter G.; Wentworth, John; Spain, Lavinia; Au-Yeung, George; Lee, Belinda; et al. (Frontiers in Endocrinology, 2023)
Hypophysitis is reported in 8.5-14% of patients receiving combination immune checkpoint inhibition (cICI) but can be a diagnostic challenge. This study aimed to assess the role of routine diagnostic imaging performed during therapeutic monitoring of combination anti-CTLA-4/anti-PD-1 treatment in the identification of hypophysitis and the relationship of imaging findings to clinical diagnostic criteria. This retrospective cohort study identified patients treated with cICI between January 2016-January 2019 at a quaternary melanoma service. Medical records were reviewed to identify patients with a documented diagnosis of hypophysitis based on clinical criteria. Available structural brain imaging with Magnetic Resonance Imaging (MRI) or computed tomography (CT) of the brain and 2deoxy-2-[ 18 F] fluoro-D-glucose Positron Emission Tomography with computed tomography (FDG-PET/CT) were assessed retrospectively. The main radiological outcome measures were a relative change in pituitary size or FDG uptake temporally attributed to cICI. 162 patients (median age 60 years, 30% female) were included. 100 and 134 had serial CT/MRI of the brain and FDG-PET/CT, respectively. 31 patients had a documented diagnosis of hypophysitis and an additional 20 had isolated pituitary imaging findings. The pituitary gland enlargement was mild, the largest absolute gland size was 13mm, with a relative increase of 7mm from baseline. There were no cases of optic chiasm compression. Pituitary enlargement and increased FDG uptake were universally transient.High-dose glucocorticoid treatment for concurrent irAEs prevented assessment of the pituitaryadrenal axis in 90% of patients with isolated imaging findings. Careful review of changes in pituitary characteristics on imaging performed for assessment of therapeutic response to iICI may lead to increased identification and more prompt management of cICI-induced hypophysitis.